Clusterin Seals the Ocular Surface Barrier in Mouse Dry Eye - Bauskar, Aditi; Mack, Wendy J.; Mauris, Jerome; Argüeso, Pablo; Heur, Martin; Nagel, Barbara A.; Kolar, Grant R.; Gleave, Martin E.; Nakamura, Takahiro; Kinoshita, Shigeru; Moradian-Oldak, Janet; Panjwani, Noorjahan; et al. (PLOS ONE, 2015)
Dry eye is a common disorder caused by inadequate hydration of the ocular surface that results in disruption of barrier function. The homeostatic protein clusterin (CLU) is prominent at fluid-tissue interfaces throughout the body. CLU levels are reduced at the ocular surface in human inflammatory disorders that manifest as severe dry eye, as well as in a preclinical mouse model for desiccating stress that mimics dry eye. Using this mouse model, we show here that CLU prevents and ameliorates ocular surface barrier disruption by a remarkable sealing mechanism dependent on attainment of a critical all-or-none concentration. When the CLU level drops below the critical all-or-none threshold, the barrier becomes vulnerable to desiccating stress. CLU binds selectively to the ocular surface subjected to desiccating stress in vivo, and in vitro to the galectin LGALS3, a key barrier component. Positioned in this way, CLU not only physically seals the ocular surface barrier, but it also protects the barrier cells and prevents further damage to barrier structure. These findings define a fundamentally new mechanism for ocular surface protection and suggest CLU as a biotherapeutic for dry eye.